Kekosongan Norma Digital Forensik dalam Penanganan Kejahatan Sumber Daya Alam (SDA): Analisis Tanggung Jawab Konstitusional Negara Pasca UU 1/2024 - Putu Khanha Khilana Putra Bukian; Ni Luh Wayan Yasmiati; Seni Kamalia Rizki Fathullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study analyzes the regulatory gaps in digital forensics regarding the handling of natural resource crimes and the state’s constitutional responsibilities following the enactment of Law No. 1 of 2024. Modern natural resource crimes, such as illegal logging and illegal mining, have evolved to leverage digital technology, leaving complex electronic traces in the form of GPS data and digital documents. However, Indonesia still faces procedural gaps in the Criminal Procedure Code (KUHAP), unclear technical standards (SNI 27037:2014 is voluntary in nature), and conflicts between the Information and Electronic Transactions Law (UU ITE) and sectoral NRE laws. This normative legal study employs legislative, conceptual, and case-based approaches. The research findings indicate that the absence of digital forensic authentication standards has fatal implications, as evidenced by the Sidoarjo District Court Decision No. 488/Pid.B/2024/PN Sda, which rejected electronic evidence. This situation constitutes state negligence (staatsverzuim) that violates Article 1(3) and Article 33(3) of the 1945 Constitution of the Republic of Indonesia. The study recommends the development of standard digital forensic procedures, the acceleration of ISO/IEC 17025 laboratory accreditation, and the harmonization of sectoral regulations